2015
DOI: 10.1038/srep12119
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing real time internal structural visualization and dynamic process monitoring in plants using synchrotron-based phase contrast X-ray imaging

Abstract: Minimally invasive investigation of plant parts (root, stem, leaves, and flower) has good potential to elucidate the dynamics of plant growth, morphology, physiology, and root-rhizosphere interactions. Laboratory based absorption X-ray imaging and computed tomography (CT) systems are extensively used for in situ feasibility studies of plants grown in natural and artificial soil. These techniques have challenges such as low contrast between soil pore space and roots, long X-ray imaging time, and low spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…After dissection of the perianth and androecium, control and heat‐stressed pistils at postanthesis (Stage V; Figure m) were also imaged following heat exposure for 4 days. The 2D projection PCI images were normalized using flat and dark images, and the X‐ray intensity images were converted into subsequent optical densities using the Beer–Lambert law (Karunakaran et al, ). All data analyses of regions of interest within flower images were carried out using ImageJ software (ImageJ 1.47v, National Institutes of Health, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After dissection of the perianth and androecium, control and heat‐stressed pistils at postanthesis (Stage V; Figure m) were also imaged following heat exposure for 4 days. The 2D projection PCI images were normalized using flat and dark images, and the X‐ray intensity images were converted into subsequent optical densities using the Beer–Lambert law (Karunakaran et al, ). All data analyses of regions of interest within flower images were carried out using ImageJ software (ImageJ 1.47v, National Institutes of Health, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The X‐ray energy of the incident beam was set to 20 keV, and a 0.5‐mm‐thick aluminium filter was used before the monochromator to reduce the heat load on the monochromator crystals. Although the accessible energy range of the BMIT‐BM is 15–40 keV, the beam energy was set to 20 keV based on previous results from Karunakaran et al (), which suggested this to be optimum for imaging above‐ground plant parts. The transmitted X‐ray images were recorded by converting the X‐ray intensities into visible images using a scintillator (comprised of Gd 2 O 2 S:Tb) combined with a visible‐light camera (which together comprise an X‐ray detector).…”
Section: Methodsmentioning
confidence: 99%
“…When X‐rays pass through the sample, interference occurs between the diffracted components of the beam and the nondiffracted portion, creating an edge‐enhanced image of the sample on the detector. Fresnel diffraction, resulting from adjustment of d , allows for control of the edge enhancement effect, which is the key feature of synchrotron‐based PCI (Karunakaran et al, ). The same principle applies to CT, which is a three‐dimensional extension of 2D‐PCI.…”
Section: Theory Behind X‐ray Pcimentioning
confidence: 99%
See 1 more Smart Citation
“…The former requires a vacuum sampling system, but the latter can only analyze elements lighter than Na. Upon development and establishment of synchrotron radiation (SR) systems, certain researchers have used X-ray fluorescence spectroscopy based on synchrotron radiation (SRXRF) and X-ray absorption spectroscopy based on synchrotron radiation (SRXAS) to image elements in plant tissues through the SR beam-line [8,15,16,17]. The SR beam-line provides a detection limit of ppm (Parts-per-million) and a space resolution near 100 nm, but one difficultly is access to a SR beam-line [18].…”
Section: Introductionmentioning
confidence: 99%